Delays in Achieving Maternal, Newborn, and Child Health Targets for 2021 and 2030 in Liberia - Laaser, Ulrich; Broniatowski, Raphael; Byepu, Stephen; Bjegovic-Mikanovic, Vesna (Frontiers in Public Health, 2019)
Objectives: The Government of Liberia has set ambitious national health targets for 2021 to reduce the high maternal, newborn, and child mortality rate and to improve the related health services. Additionally, Sustainable Development Goal 3 provides a long-term target for 2030. The objective of this article is to analyze the gaps between the targets and collected data. Materials and Methods: Relevant national documents were scrutinized to identify targets and related indicators which can serve as benchmarks for future achievements in Liberia's maternal, newborn, and child health. For each indicator, progress observed will be compared with that needed to meet the target, based on the indicator value in a baseline year, a later observed value, and the expected value in 2021 and 2030, respectively. Results: The Gap Analysis reveals achievements and serious delays for 21 health and health system indicators. Based on national data the reduction of the maternal mortality ratio will take an additional −8.2 years for the 2021 target and −12.5 years for the 2030 target. The Neonatal Mortality rate is experiencing similar delays of −7.9 years for 2021 and −12.9 for 2030 whereas the targets for the Under-5-Mortality rate can be achieved with small delays of −1.8 and −1.7 years. Conclusions: The Government of Liberia requires persistent efforts and international support to achieve its national targets and the Sustainable Development Goal 3 for health.